2022
DOI: 10.1371/journal.pone.0261827
|View full text |Cite
|
Sign up to set email alerts
|

How can the education sector support children’s mental health? Views of Australian healthcare clinicians

Abstract: Objectives Policy makers in developed countries have long considered the education system an avenue for supporting mental health care for children. Whilst educators have identified many challenges to providing this support (e.g. non-core role, stigma, overcrowded curriculum), understanding clinicians’ views on the role of educators and schools and how clinicians and schools could work together to achieve good mental health outcomes are important questions. However, clinician voices in how schools and health sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Such occasions of special support would lead children to increase the amount of close contact with a teacher and contribute to better mental health even if the special support is not aimed at caring for the mental health of children. Previous studies have reported that interactions between teachers and students are associated with better mental health among children 34,35 . Probably, children who used only non‐Japanese at home may have lower Japanese skills than those who use both languages more often, therefore children who speak only foreign languages might have more occasions to receive special support in schools, and these occasions may contribute to the better mental health of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such occasions of special support would lead children to increase the amount of close contact with a teacher and contribute to better mental health even if the special support is not aimed at caring for the mental health of children. Previous studies have reported that interactions between teachers and students are associated with better mental health among children 34,35 . Probably, children who used only non‐Japanese at home may have lower Japanese skills than those who use both languages more often, therefore children who speak only foreign languages might have more occasions to receive special support in schools, and these occasions may contribute to the better mental health of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that interactions between teachers and students are associated with better mental health among children. 34 , 35 Probably, children who used only non‐Japanese at home may have lower Japanese skills than those who use both languages more often, therefore children who speak only foreign languages might have more occasions to receive special support in schools, and these occasions may contribute to the better mental health of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Estas bondades permiten inferir que las opiniones de los médicos (Paton et al, 2022) y los miembros del equipo de salud se debe tomar en cuenta sobre cómo el sistema educativo podría apoyar la salud mental de los estudiantes y mejorar el acceso a la atención de salud mental para niños y adolescentes.…”
Section: Tabla 4 Efectividad Del Programa Educativo En El Fortalecimi...unclassified
“…Adolescents with mental health problems are more vulnerable to academic failure, dropping out of school, substance abuse, criminal/legal involvement, and exploitation [21]. Schools play an essential role in supporting many young people's mental health and can also enable early intervention when displaying symptoms [22]. The school setting also provides an opportunity to reach large numbers of young people simultaneously [23].…”
Section: Introductionmentioning
confidence: 99%